Chromosome-level genome assembly reveals the unique genome evolution of the swimming crab (Portunus trituberculatus). Issue 1 (6th January 2020) - Tang, Boping; Zhang, Daizhen; Li, Haorong; Jiang, Senhao; Zhang, Huabin; Xuan, Fujun; Ge, Baoming; Wang, Zhengfei; Liu, Yu; Sha, Zhongli; Cheng, Yongxu; Jiang, Wei; et al.
Abstract: Background: The swimming crab, Portunus trituberculatus, is an important commercial species in China and is widely distributed in the coastal waters of Asia-Pacific countries. Despite increasing interest in swimming crab research, a high-quality chromosome-level genome is still lacking. Findings: Here, we assembled the first chromosome-level reference genome of P. trituberculatus by combining the short reads, Nanopore long reads, and Hi-C data. The genome assembly size was 1.00 Gb with a contig N50 length of 4.12 Mb. In addition, BUSCO assessment indicated that 94.7% of core eukaryotic genes were present in the genome assembly. Approximately 54.52% of the genome was identified as repetitive sequences, with a total of 16, 796 annotated protein-coding genes. In addition, we anchored contigs into chromosomes and identified 50 chromosomes with an N50 length of 21.80 Mb by Hi-C technology. Conclusions: We anticipate that this chromosome-level assembly of the P. trituberculatus genome will not only promote study of basic development and evolution but also provide important resources for swimming crab reproduction.